The Influence of Work Environment And Work Disicipline on Employee Performance In Restaurants Kitchen Kraton Baros City Cimahi - Ayi Muhiban; Abid Naufal (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was carried out on employees of the Dapur Kraton Baros restaurant, Cimahi City. The purpose of this study is to ascertain how much employees of the Dapur Kraton Baros restaurant in Cimahi City are affected by their work environment and work discipline, both concurrently and partially. Both descriptive and associative research methodologies were used in this study. The individual in this study is as the analysis component, they are the staff members of the Dapur Kraton Baros restaurant in Cimahi City. The study's sample comprised thirty-one participants. Due to the fact that every member of the population—that is, every employee of the Dapur Kraton restaurant in Cimahi City—was chosen as a sample, this study employed a saturated sample. The validity and reliability of the study instruments were tested as part of the analysis process, which also included multiple linear regression analysis. According to the study's findings, there is a partial and simultaneous influence on exogenous variables (workplace culture and work ethic) on endogenous variables (performance). According to the research, employees should be able to enhance poorly enforced work discipline, reassess the workspace to ensure optimal efficiency, and enhance both the quality and quantity of their job output